RESPON ANOA GUNUNG (Bubalus quarlesi) TERHADAP MANIPULASI PAKAN PADA KONDISI PRABUDIDAYA - Moh. Basri (Universitas Tadulako, 2008)
In Indonesia, meat supply is much less than the demand. The national meat production in 2006 was 2.070.234 t year-1 (DJP 2006) whereas the demand for meat was 2,957,477 t year -1. In Central Sulawesi forest, anoa has been utilized by the people around the forest as an alternative animal meat to meet their demand for meat. A mountainous anoa has an average body weight of 40 kg and fresh feed intake of 7-10 kg day-1 animal-1. The biological characteristics of anoa allow the anoa to be domesticated easily as a source of meat animal in the areas around the forest. There is a lack of study in the aspect of anoa meat nutrition; as a consequence information on such aspect is limited. Thus, information about anoas response on feed manipulation is necessary. The present experiment was conducted to study the responses of anoas on feed manipulation. The experiment was conducted in Palu, Province of Central Sulawesi. Feeding trials were designed to study the effect of combination of pokae fruits and spinach levels in feed on feed intake, weight gain (WG) and feed efficiency. The treatments were allocated in a 6 x 6 Latin Square design. Analysis of variance and Duncan’s test were applied to analyze the data obtained. Feeding of 5 kg pokae and 1.5 kangkung (R4(5.0/1.5)) diet resulted in the highest intake dry matter, crude protein, Ca, P ,crude fiber, and weight gain of 1.29 kg, 0.60 kg TDN, 0.17 kg, 0.0124 kg and 0.0103 kg, 0.46 kg and 0.516 kg day-1 animal-1, and feed efficiency of 4.3%.